Incorporation of Hydrophilic Macrocycles Into Drug-Linker Reagents Produces Antibody-Drug Conjugates With Enhanced in vivo Performance - Evans, Nick; Grygorash, Ruslan; Williams, Paul; Kyle, Andrew; Kantner, Terrence; Pathak, Ravindra; Sheng, XiaoBo; Simoes, Fabio; Makwana, Hiteshri; Resende, Ricardo; de Juan, Elena; Jenkins, Alan; et al. (Frontiers in Pharmacology, 2022)
Antibody-drug conjugates (ADCs) have begun to fulfil their promise as targeted cancer therapeutics with ten clinical approvals to date. As the field matures, much attention has focused upon the key factors required to produce safe and efficacious ADCs. Recently the role that linker-payload reagent design has on the properties of ADCs has been highlighted as an important consideration for developers. We have investigated the effect of incorporating hydrophilic macrocycles into reagent structures on the in vitro and in vivo behavior of ADCs. Bis-sulfone based disulfide rebridging reagents bearing Val-Cit-PABC-MMAE linker-payloads were synthesized with a panel of cyclodextrins and crown ethers integrated into their structures via a glutamic acid branching point. Brentuximab was selected as a model antibody and ten ADCs with a drug-to-antibody ratio (DAR) of 4 were prepared for biological evaluation. In vitro, the ADCs prepared showed broadly similar potency (range: 16-34 pM) and were comparable to Adcetris® (16 pM). In vivo, the cyclodextrin containing ADCs showed greater efficacy than Adcetris® and the most efficacious variant (incorporating a 3'-amino-α-cyclodextrin component) matched a 24-unit poly(ethylene glycol) (PEG) containing comparator. The ADCs bearing crown ethers also displayed enhanced in vivo efficacy compared to Adcetris®, the most active variant (containing a 1-aza-42-crown-14 macrocycle) was superior to an analogous ADC with a larger 24-unit PEG chain. In summary, we have demonstrated that hydrophilic macrocycles can be effectively incorporated into ADC reagent design and offer the potential for enhanced alternatives to established drug-linker architectures.